Home based management in multiple sclerosis: results of a randomised controlled trial. Issue 3 (1st September 2002) - Pozzilli, C; Brunetti, M; Amicosante, A M V; Gasperini, C; Ristori, G; Palmisano, L; Battaglia, M
Abstract : Background: Home based medical care is a popular alternative to standard hospital care but there is uncertainty about its cost-effectiveness. Objectives: To compare the effectiveness and the costs of multidisciplinary home based care in multiple sclerosis with hospital care in a prospective randomised controlled trial with a one year follow up. Methods: 201 patients with clinically definite multiple sclerosis were studied. They were randomised in a ratio 2:1 to an intervention group (133) or a control group (68). They were assessed at baseline and one year after randomisation with validated measures of physical and psychological impairment and quality of life (SF-36 health survey). The costs to the National Health Service over the one year follow up were calculated by a cost minimisation analysis. Results: There were no differences in functional status between the home based care group and the hospital group. There was a significant difference between the two groups favouring home based management in four SF-36 health dimensions—general health, bodily pain, role-emotional, and social functioning (all p ≤ 0.001). The cost of home based care was slightly less (822 euros/patient/year) than hospital care, mainly as a result of a reduction in hospital admissions. Conclusions: Comprehensive planning of home based intervention implemented by an interdisciplinary team and designed specifically for people with multiple sclerosis may provide a cost-effective approach to management and improve the quality of life.